Attractions, Activities and Accessibility Assessment for Religious Tourism Destination Development Planning in Soibada, Timor-Leste - Vong, Emanuel (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Every year, especially in May and October, thousands of Catholics pilgrimage to the Sagrado Coracao de Jesus Church and the Chapel of Nossa Senhora de Aitara on Aitara Hill with various Catholic religious activities in Soibada. In the development of religious tourism destinations, planning and assessment are needed using indicators of attractions, activities, and accessibility of religious tourism. This study aims to explore the potential for developing tourist areas in Soibada for the development of religious tourism through indicators of attractions and religious activities that have existed so far. This study uses some of the data from the research used to prepare the strategic plan of the ATR-TL (Association of Religious Tourism of Timor-Leste) in 2022 and is analyzed using a quantitative approach, SWOT analysis as a form of assessment and evaluation with the intended indicators. The results of this study are: Soibada as a tourist destination has strengths, many authentic advantages, and uniqueness that must be conserved and are possible for the development and sustainability of religious tourism in Soibada, Manatuto Municipality, and Timor-Leste in general. Planning and development of religious tourism destinations in Soibada must maintain and improve the strength and opportunity factors, on the other hand, it must also pay attention to the elements of weakness and threat.